Group vocal composition and decision-making during roost finding in Spix’s disk-winged bats - Sagot, Maria (2024)
Theoretical work suggests that having many informed individuals within social groups can promote efficient resource location. However, it may also give rise to group fragmentation if members fail to reach consensus on their direction of movement. In this study, we investigate whether the number of informed individuals, exemplified by bats emitting calls from different roosts, influences group cohesion in Spix’s disk-winged bats (Thyroptera tricolor). Additionally, we explore the role of signal reliability, quantified through signalling rates, in group consensus on where to roost. These bats use contact calls to announce the location of a roost site and recruit conspecifics. The groups they form exhibit high levels of cohesion and consist of both vocal and non-vocal bats, with vocal behaviour being consistent over time. Our findings revealed that an increase in the number of roosts broadcasting calls is strongly associated with the likelihood of groups fragmenting among multiple roosts. Additionally, we found that a majority of group members enter the roost with higher calling rates. This phenomenon can mitigate the risk of group fragmentation, as bats emitting more calls may contribute to greater group consensus on roosting locations, thereby reducing the likelihood of individuals separating and enhancing overall group cohesion. Our results highlight the potential costs of having too many information producers for group coordination, despite their established role in finding critical resources.